A systematic literature review of the association between global brain atrophy and the Expanded Disability Status Scale score in people with multiple sclerosis - Zivadinov, Robert; Le, Hoa H.; Keenan, Alexander; Stocks, Susan Jill (Therapeutic advances in neurological disorders, 2025)
Brain atrophy (BA) is a useful predictor of clinical outcomes in people with multiple sclerosis (PwMS). For this reason, MAGNIMS (Magnetic Resonance Imaging in Multiple Sclerosis), an expert consensus group, recommended that global brain volume loss (BVL) is included as a secondary outcome in therapeutic clinical trials. However, there has not been a recent review of the evidence of the association, or strength of association, between global BA and disability in PwMS. Our aim is to review articles from 2013 onward measuring the associations between percentage of brain volume loss (PBVL), normalized brain volumes (NBV) or normalized brain parenchymal volume (NBPV), and the Expanded Disability Status Scale (EDSS), or disability progression (DP) measured by EDSS in PwMS. Systematic review. We searched Medline, Embase, Cochrane Library, Cochrane Clinical Register of Controlled Trials, Cochrane Database of Systematic Reviews and Cumulative Index to Nursing and Allied Health Literature for observational studies, clinical trials and modelling studies measuring the association between global BVL, PBVL, NBV or NBPV, and EDSS score or DP in PwMS. We included people with clinically isolated syndrome and excluded studies with a population greater than 20% primary progressive multiple sclerosis patients. We found 58 studies were eligible for the review. Most longitudinal studies (19/23) observed a significant association between global BVL and change in EDSS score or DP. Similarly the majority of cross-sectional studies (26/29) observed an association between baseline BV measures and EDSS. Most studies investigating the association between baseline brain volume (BV) measures and follow-up EDSS, that is, asking if baseline BV is a predictor of DP, or future EDSS score, did not find an association (4/15 observed an association). Around a 1% (range 0.4%-1.3%) decrease in global BV per year was associated with DP, but caution in comparing studies is recommended due to variations in the definition of DP.